Communication and cultural interaction in health promotion strategies to migrant populations in Italy: the cross-cultural phone counselling experience - Filippo Maria Taglieri; Anna Colucci; Donatella Barbina; Emanuele Fanales-Belasio; Anna Maria Luzi (Istituto Superiore di Sanità, 2013)
INTRODUCTION: In the last 10 years migration processes have progressively increased worldwide and in Italy about 5 millions of residing migrants are estimated. To meet health needs of these new residents, effective relational and communication tools, which allow a reciprocal intercultural interaction within health care structures, are therefore necessary. AIM: This article faces the main features of the relational-communication processes associated with health promotion and care in the migrant population in Italy to the aim of identifying the key and critical points within the interaction between different cultures, focusing on the role of specific professional figures, including cultural mediators and health educators. RESULTS: Within the activity of HIV phone counselling operated by Psyco-socio-behavioural, Communication and Training Operating Unit of National Institute of Health in Italy, an intercultural approach was successfully experienced in a project targeted to migrants (2007-2008). Specifically, the presence of cultural mediators answering in the languages of main migrants' groups allowed the increase of calls from migrant people and of the information provided.